2023
DOI: 10.1088/1555-6611/acbcd4
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of optical fiber laser based on super-mode interference in a seven-core fiber

Abstract: Tuning of optical fiber laser emissions based on super-mode interference in a seven core fiber (SCF) is presented. This super-mode interference is generated by a super-mode Mach–Zehnder interferometer constructed with a few millimeters of SCF spliced between two single mode fibers (SMFs). In the SCF, two super-modes are exited via the fundamental mode of the SMF. Then, an interference pattern caused to the optical path difference between super-modes is generated at the final of the SCF, which is collected with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…We have indicated the operation wavelength in Figure 1 as a vertical dotted line and labeled it Λ 0 . On the other hand, it has been demonstrated that bending SMF-MCF-SMF devices translates into a high-sensitivity spectral shift [ 37 , 38 , 39 , 40 ]. Therefore, the spectral response of the proposed device can be set to intersect the operation wavelength at half the normalized intensity, provided a bending-based shift φ B .…”
Section: Principle Of Operationmentioning
confidence: 99%
“…We have indicated the operation wavelength in Figure 1 as a vertical dotted line and labeled it Λ 0 . On the other hand, it has been demonstrated that bending SMF-MCF-SMF devices translates into a high-sensitivity spectral shift [ 37 , 38 , 39 , 40 ]. Therefore, the spectral response of the proposed device can be set to intersect the operation wavelength at half the normalized intensity, provided a bending-based shift φ B .…”
Section: Principle Of Operationmentioning
confidence: 99%
“…These filters usually consist of special structures to achieve interference effects, thus achieving multi-wavelength laser output, such as Michelson [9][10] , Mach-Zendel [11] , Fabry-Perot [12] , and Zagnac [13] interferometers. Mach-Zendel interferometer is one of the most used and widely used interferometers, and has been fabricated for gratings [14] , pull cones [15] , photonic crystal fibers [16] , multi-core fibers [17][18] , etc. In 2019, Salceda-Delgado et al proposed wavelength switchable and tunable fiber lasers by using a tunable intra-cavity filter based on a modal Michelson interferometer.…”
Section: Introductionmentioning
confidence: 99%